Allergic rhinitis associated with the degree of pulmonary involvement due to covid-19 in patients from a peruvian general hospital - García-Gallo, Bianca (2023)
Objectives. To evaluate the association between allergic rhinitis and the degree of pulmonary involvement in patients with COVID-19 and to determine the frequencies of the main variables. Materials and methods. An observational, cross-sectional and analytical study was carried out by reviewing the medical records of patients diagnosed with COVID-19 from the Cayetano Heredia National Hospital between 2020 and 2021. We obtained information regarding the history of allergic rhinitis; pulmonary involvement was assessed by non-contrast tomography results using the chest computed tomography (CT) score. Data regarding sociodemographic and clinical variables was also obtained. Both crude (PR) and adjusted (aPR) prevalence ratios with their respective 95% confidence intervals (CI) were estimated. We also used a generalized linear Poisson family model with log link function and robust variances. Results. We evaluated 434 patients, who were mostly male, older than 60 years and had no relevant medical history. Of these, 56.2% had a history of allergic rhinitis and 43.1% had moderate to severe pulmonary involvement. The adjusted regression model showed that the history of allergic rhinitis reduced the severity of COVID-19 according to the pulmonary involvement assessed by the CT score (aPR: 0.70; 95%CI: 0.56-0.88; p=0.002). Conclusions. The history of allergic rhinitis resulted in a 30.0% decrease in COVID-19 severity according to the CT score in hospitalized patients.